Pemberdayaan Masyarakat Melalui Kelompok Tani Perindu di Kelurahan Lubuk Minturun Kota Padang - Ade Vita Putri; Irmawita Irmawita (Jurnal Family Education, 2023)
This research is motivated by the phenomenon of the development of longing farmer groups which cannot be separated from community empowerment programs through mentoring, counseling and services. This matter helps farmers in improving the standard of living of farmers. This research is a quantitative descriptive type of research. The population in this study are members of the Perindu Farmers Group in Lubuk Minturun Village, totaling 26 people. The sampling technique used is simple random sampling, 19 samples were taken. Data collection techniques using a questionnaire. Meanwhile, the data analysis technique used is the percentage formula. The results showed that community empowerment through the Perindu Farmers Group in Lubuk Minturun Village, Padang City was categorized in terms of very supportive assistance, very supportive in terms of counseling and in terms of services it was categorized as supportive.